2020
DOI: 10.21608/bvmj.2020.25678.1186
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic characterization of some foodpoisoning bacteria isolated from meat and meat products in Kaliobia, Egypt

Abstract: The present study was performed on 250 random samples of fresh meat and meat products. Beef burger, kofta, minced meat and sausage (50 for each) were collected from different shops (25gm of each sample) at Kaliobia Governorate, Egypt, to detect the prevalence of some toxigenic food-borne bacteria, beside the phenotypic characterization and detection of some virulence genes. Bacteriological examination of the collected samples resulted in an isolation of Staph. aureus isolates (41/16.4%), E. coli (25 /10.0%), B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 8 publications
3
1
0
Order By: Relevance
“…S.aureus showed sensitivity to norfloxacin (19mm), gentamycin (18mm) and ciprofloxacin (22mm); while the organisms was found resistant to neomycin (7mm), erythromycin (6mm), streptomycin (2mm), tetracycline (3mm) and ampicillin (5mm). Our results were in agreement with Gamal et al (2020) who stated that S.aureus was highly sensitive to norfloxacin, gentamycin, ciprofloxacin and resistant against ampicillin, methicillin, oxytetracycline, streptomycin and erythromycin. Owuna et al (2015) reported the high sensitivity against gentamycin, ciprofloxacin, erythromycin and amoxicillin.…”
Section: Antimicrobial Sensitivitysupporting
confidence: 93%
See 3 more Smart Citations
“…S.aureus showed sensitivity to norfloxacin (19mm), gentamycin (18mm) and ciprofloxacin (22mm); while the organisms was found resistant to neomycin (7mm), erythromycin (6mm), streptomycin (2mm), tetracycline (3mm) and ampicillin (5mm). Our results were in agreement with Gamal et al (2020) who stated that S.aureus was highly sensitive to norfloxacin, gentamycin, ciprofloxacin and resistant against ampicillin, methicillin, oxytetracycline, streptomycin and erythromycin. Owuna et al (2015) reported the high sensitivity against gentamycin, ciprofloxacin, erythromycin and amoxicillin.…”
Section: Antimicrobial Sensitivitysupporting
confidence: 93%
“…. Our results are agreed with Gamal et al (2020) who reported that B.cereus isolates were susceptible to gentamycin, norfloxacin, and ciprofloxacin; while resistant against ampicillin, oxytetracycline, streptomycin, neomycin and erythromycin. Mousa et al (2020) described antibiotic resistant B.cereus in Kaliobia Egypt and reported 82.3% sensitivity to both gentamycin and norfloxacin, 74.5% to ciprofloxacin and resistant against ampicillin, and oxytetracycline; whereas intermediate sensitivity showed against streptomycin, erythromycin and neomycin.…”
Section: Antimicrobial Sensitivitysupporting
confidence: 93%
See 2 more Smart Citations
“…In contrast to the present study, Wei et al (2006) reported a lower prevalence rate of E. coli obtained from ready to eat food products stored in the refrigerator and room temperatures showed the prevalence rates of E. coli with 3% (1/40) and 2% (1/44), respectively. Gamal et al (2020) also reported a low prevalence rate of E. coli from sausage 10.0% (5/50). All these low prevalence rate of E. coli reported by these researchers might be due to the proper hygienic status of the butcher, systematic sanitation education systems of employee, proper cleanliness of utensils and equipment and continuous monitoring of the microorganisms.…”
Section: Resultsmentioning
confidence: 93%